Ginseng pharmacology: a new paradigm based on gintonin-lysophosphatidic acid receptor interactions - Choi, Sun-Hye; Jung, Seok-Won; Lee, Byung-Hwan; Kim, Hyeon-Joong; Hwang, Sung-Hee; Kim, Ho-Kyoung; Nah, Seung-Yeol (Frontiers in Pharmacology, 2015)
Ginseng, the root of Panax ginseng, is used as a traditional medicine. Despite the long history of the use of ginseng, there is no specific scientific or clinical rationale for ginseng pharmacology besides its application as a general tonic. The ambiguous description of ginseng pharmacology might be due to the absence of a predominant active ingredient that represents ginseng pharmacology. Recent studies show that ginseng abundantly contains lysophosphatidic acids (LPAs), which are phospholipid-derived growth factor with diverse biological functions including those claimed to be exhibited by ginseng. LPAs in ginseng form a complex with ginseng proteins, which can bind and deliver LPA to its cognate receptors with a high affinity. As a first messenger, gintonin produces second messenger Ca2+ via G protein-coupled LPA receptors. Ca2+ is an intracellular mediator of gintonin and initiates a cascade of amplifications for further intercellular communications by activation of Ca2+-dependent kinases, receptors, gliotransmitter and neurotransmitter release. Ginsenosides, which have been regarded as primary ingredients of ginseng, cannot elicit intracellular [Ca2+]i transients, since they lack specific cell surface receptor. However, ginsenosides exhibit non-specific ion channel and receptor regulations. This is the key characteristic that distinguishes gintonin from ginsenosides. Although the current discourse on ginseng pharmacology is focused on ginsenosides, gintonin can definitely provide a mode of action for ginseng pharmacology that ginsenosides cannot. This review article introduces a novel concept of ginseng ligand-LPA receptor interaction and proposes to establish a paradigm that shifts the focus from ginsenosides to gintonin as a major ingredient representing ginseng pharmacology.